Collecting and Archiving Modern and Contemporary Art on the African Continent - Cluster Project (Presenting The Cluster Projects, 2021)
Dr. Ulf Vierke, director of Bayreuth's Iwalewahaus, talks about his project: "Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent" Find more information here: https://www.africamultiple.uni-bayreuth.de/en/Research/1research-sections/art_aestethics/Of-Art-Worlds/index.html